Effect of Oxalic Acid Treatment on Sediment Arsenic Concentrations and Lability under Reducing Conditions - Sun, Jing (J Hazard Mater, 2016)
Oxalic acid enhances arsenic (As) mobilization by dissolving As host minerals and competing for sorption sites. Oxalic acid amendments thus could potentially improve the efficiency of widely used pump-and-treat (P&T) remediation. This study investigates the effectiveness of oxalic acid on As mobilization from contaminated sediments with different As input sources and redox conditions, and examines whether residual sediment As after oxalic acid treatment can still be reductively mobilized. Batch extraction, column, and microcosm experiments were performed in the laboratory using sediments from the Dover Municipal Landfill and the Vineland Chemical Company Superfund sites. Oxalic acid mobilized As from both Dover and Vineland sediments, although the efficiency rates were different. The residual As in both Dover and Vineland sediments after oxalic acid treatment was less vulnerable to microbial reduction than before the treatment. Oxalic acid could thus improve the efficiency of P&T. X-ray absorption spectroscopy analysis indicated that the Vineland sediment samples still contained reactive Fe(III) minerals after oxalic acid treatment, and thus released more As into solution under reducing conditions than the Dover samples. Therefore, the efficacy of P&T must consider sediment Fe mineralogy when evaluating its overall potential for remediating groundwater As.